Processions: studies of Bronze Age ritual and ceremony presented to Robert B. Koehl - Weingarten, Judith; Macdonald, Colin F.; Aruz, Joan; Fabian, Lara; Kumar, Nisha (Archaeopress, 2023)
Robert Koehl has long considered processions to have played an integral role in Aegean Bronze Age societies. Papers concentrate mainly on evidence from Crete, the Cyclades and the Greek mainland, with additional perspectives from abroad, these geographic divisions forming the basic outline of this volume.
Description based on publisher supplied metadata and other sources
Keywords: Greece -- Antiquities; Greece; Grèce - Antiquités; Festschrift; Minoische Kultur; Kreta